Breath testing for intra-abdominal infection: appendicitis, a preliminary study. (20th October 2020) - Andrews, B T; Das, P; Denzer, W; Ritchie, G A; Peverall, R; Hamade, A M; Hancock, G
Abstract: In the current pilot study we aimed to determine whether breath analysis could be used to help recognise intra-abdominal infection, using acute appendicitis as an exemplar condition. Our study included 53 patients (aged 18–88 years) divided into three groups: appendix group, 26 (13 male) patients suffering from acute appendicitis; control group 20 (seven male) patients undergoing elective abdominal surgery; normal group, seven patients who were clinically diagnosed with appendicitis, but whose appendix was normal on histological examination. Samples of breath were analysed using ion molecule reaction mass spectroscopy measuring the concentration of volatile compounds (VCs) with molecular masses 27–123. Intraperitoneal gas samples were collected from a subset of 23 patients (nine diagnosed with acute appendicitis). Statistically significant differences in the concentration of VCs in breath were found between the three groups. Acetone, isopropanol, propanol, butyric acid, and further unassigned VCs with molecular mass/charge ratio (m/z) 56, 61 and 87 were all identified with significant endogenous contributions. Principle component analysis was able to separate the control and appendicitis groups for seven variables: m/z = 56, 58, 59, 60, 61, 87 and 88. Comparing breath and intraperitoneal samples showed significant relationships for acetone and the VC with m/z = 61. Our data suggest that it may be possible to help diagnose acute appendicitis by breath analysis; however, factors such as length of starvation remain to be properly accounted for and the management or mitigation of background levels needs to be properly addressed, and larger studies relating breath VCs to the causative organisms may help to highlight the relative importance of individual VCs.